Mein aur Mera Dost - Yasmeen Muzaffer (Karachi Oxford University Press, 2016)
Written in a simple yet attractive style, Mein aur Mera Dost revolves around two friends, one of whom has a disability. Through this story, the writer has endeavoured to educate children to befriend those who are less fortunate or have special needs. Such friendships can play an important role in confidence building and rehabilitation of children with special needs and help them overcome all barriers and become honourable members of society.
Includes Colored Illustrations.
Keywords: Stories for Children